DEVELOPMENT OF STUDENT WORKSHEETS ON THE PERIODIC SYSTEM OF ELEMENTS BASED ON CONTEXTUAL TEACHING AND LEARNING FOR PHASE-E SENIOR HIGH SCHOOL - Risty, Chika Mei; Kurniawati, Desy; Hardeli, Hardeli; Zainul, Rahadian; Syolendra, Dwi Finna (Chimica Didactica Acta, 2024)
This study aimed to produce teaching materials in student worksheets based on contextual teaching and learning and to determine the validity and practicality of the student worksheets developed. The research method used is educational design research (EDR), with the Plomp development model carried out until the validity and practicality test stages are achieved. This development research shows that the contextual teaching and learning-based student worksheets developed are valid and practical. This is supported by the validation results, which have an average value of 0.91 and are included in the very valid category. The practicality results obtained from the small group test of students get a percentage of 95%, and the percentage result from the teacher is 92%, which is included in the Highly practical category. These results indicate that the student worksheets developed are feasible to be applied to learning to help students' understanding of concepts on the material of the periodic system of elements and encourage students to become active, creative, and critical learners. The results of this study indicate that the student worksheets developed are suitable for use in the learning process on the material of the periodic system of elements in phase E Senior High School.